CdWRKY2 transcription factor modulates salt oversensitivity in bermudagrass [Cynodon dactylon (L.) Pers.] - Shao, An; Xu, Xiao; Amombo, Erick; Wang, Wei; Fan, Shugao; Yin, Yanling; Li, Xiaoning; Wang, Guangyang; Wang, Hongli; Fu, Jinmin (Frontiers in Plant Science, 2023)
Common Bermudagrass (Cynodon dactylon (L.) Pers.) has higher utilization potential on saline soil due to its high yield potential and excellent stress tolerance. However, key functional genes have not been well studied partly due to its hard transformation.Here, bermudagrass "Wrangler" successfully overexpressing CdWRKY2 exhibited significantly enhanced salt and ABA sensitivity with severe inhibition of shoots and roots growth compared to the transgenic negative line. The reduced auxin accumulation and higher ABA sensitivity of the lateral roots (LR) under salt stress was observed in CdWRKY2 overexpression Arabidopsis lines. IAA application could rescue or partially rescue the salt hypersensitivity of root growth inhibition in CdWRKY2 overexpressing Arabidopsis and Bermudagrass respectively. Subsequent experiment in Arabidopsis indicated that CdWRKY2 could directly bind to the promoter region of AtWRKY46 and down-regulated its expression to further up-regulate the expression of ABA and auxin pathway-related genes. Besides, CdWRKY2 overexpression in mapk3 background Arabidopsis could partly rescue the salt-inhibited LR growth caused by CdWRKY2 overexpression. These results indicated that CdWRKY2 could negatively regulate LR growth under salt stress via the regulation of ABA signaling and auxin homeostasis, which partly rely on AtMAPK3 function. CdWRKY2 and its homologue genes, could also be useful targets for genetic engineering of salinity-tolerance plants.